2007
DOI: 10.1243/09544070jauto471
|View full text |Cite
|
Sign up to set email alerts
|

Steering control of six-wheeled vehicles using linear quadratic regulator techniques

Abstract: The middle- and rear-wheel steering angles of a six-wheeled vehicle need to be coordinated with the front-wheel steering angle to obtain the maximum manoeuvrability. A steering control strategy using the linear quadratic regulator technique with integral control is proposed in this paper such that both zero side-slip angle and target yaw rate following can be achieved simultaneously. An estimator to be used with the control law is also designed to provide the estimate of side-slip angle. AutoSim is used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…34 Hence, the weights matrices Q and R are continuously optimized for each design parameter variation to ensure asymptotic stability with real negative eigenvalues of the closed-loop control system. The weights matrices Q and R are presented according to Bryson's rule [35][36][37] and optimized based on a free constant positive number C Q , the maximum allowable average steering angle of the 3rd and 4th (d 3max: and d 4max: ) as in equations (16) and (17), consequently. For that purpose, a new cost function is synthesized and introduce as in equation (18).…”
Section: Optimal Gslqrmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Hence, the weights matrices Q and R are continuously optimized for each design parameter variation to ensure asymptotic stability with real negative eigenvalues of the closed-loop control system. The weights matrices Q and R are presented according to Bryson's rule [35][36][37] and optimized based on a free constant positive number C Q , the maximum allowable average steering angle of the 3rd and 4th (d 3max: and d 4max: ) as in equations (16) and (17), consequently. For that purpose, a new cost function is synthesized and introduce as in equation (18).…”
Section: Optimal Gslqrmentioning
confidence: 99%
“…Huh et al 15 compared different steering configurations of a 6-wheel vehicle. The study showed that the handling characteristics of the vehicle are improved in case of 6-Wheel Steering (6 WS) than other configurations which were improved later by Chen et al 16 using Linear Quadratic Regulator (LQR) controller. Later, an optimal 6 WS controller was introduced by Kim, Yi, and Lee 17 and Kim et al 18 by constraining the lateral force to the friction circle.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ARS seems to be more efficient for military combat vehicles as it works in a harsh environment, so noise will not be an issue, and it requires a trained driver to operate it. Despite that, limited studies considered ARS to improve lateral stability of combat vehicles as in [15][16][17] and in 18,19 for a 6x6 and 8 × 8 combat vehicles, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the early days of dynamical investigation, various scholars extended the vehicle-handling concepts and traditional conventions commonly found in literature relevant to two-axle vehicles, to the three-axle models. Then, some of them developed steering control strategies or controllers based on these three-axle models, such as the linear quadratic regulator technique with integral control (Chen et al, 2007), desired yaw rate (An et al, 2008), and the model-following variable structure (Qu et al, 2008), were analogous to the techniques of the two-axle vehicle. To further improve vehicle stability and manoeuvrability, Shen et al (2016) developed a direct yaw moment control method based on an 8-axle vehicle with 16-independent driving wheels.…”
Section: Introductionmentioning
confidence: 99%